2020
DOI: 10.1177/1559325820907016
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: MiR-142-5p Protects Against 6-OHDA-Induced SH-SY5Y Cell Injury by Downregulating BECN1 and Autophagy

Abstract: Background: MiR-142-5p has been demonstrated to hold significant implications in neurological diseases. However, the impact and underlying regulatory mechanism of miR-142-5p in Parkinson’s disease (PD) are still ominous. Methods: To simulate the PD, 6-hydroxydopamine (6-OHDA)-treated SH-SY5Y cell model was used in this study. Levels of messenger RNA and protein were tested by quantitative real-time polymerase chain reaction and Western blot analyses, respectively. The direct interaction between miR-142-5p and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It is reported that miR-142-5p is downregulated in 6-OHdA-treated SH-SY5Y cells, and its upregulation enhances neuronal vitality by suppressing Beclin-1-dependent autophagy, implying a neuroprotective role of miR-142-5p in the progression of Pd (72). In addition to targeting ATGs, miRNAs have been implicated in the regulation of autophagy-related signaling pathways in Pd.…”
Section: Roles Of Autophagy-regulating Mirnas In Pdmentioning
confidence: 99%
“…It is reported that miR-142-5p is downregulated in 6-OHdA-treated SH-SY5Y cells, and its upregulation enhances neuronal vitality by suppressing Beclin-1-dependent autophagy, implying a neuroprotective role of miR-142-5p in the progression of Pd (72). In addition to targeting ATGs, miRNAs have been implicated in the regulation of autophagy-related signaling pathways in Pd.…”
Section: Roles Of Autophagy-regulating Mirnas In Pdmentioning
confidence: 99%
“…ADAMTS9-AS1, a long-stranded non-coding RNA, inhibits the progression of PCa by regulating the miR-142-5p/CCND1 axis [30], and miRNA-186-5p inhibits the proliferation, anchorage-independent growth, and invasion of metastatic PCa cells [31]. The results highlight that miR-142-5p functions as a neuroprotective regulator in 6-OHDA-induced neuronal SH-SY5Y cells simulating the PD model in vitro via regulating autophagy-related protein beclin 1 (BECN1) and autophagy to influence cell viability [32]. Studies have shown that the downregulation of circ-CCNB2 could promote the radiosensitivity of PCa by inhibiting autophagy through the miR-30b-5p/KIF18A axis, thus establishing the molecular resistance mechanism of radiotherapy for PCa and a feasible strategy to improve radiosensitivity [33].…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y cells in good conditions were treated with different concentrations (10, 50, 100, 150, and 200 μM) of 6-OHDA (Sigma-Aldrich, Merck KGaA, Darmstadt, Germany) for different time (0, 3, 6, 12, 24, and 48 h) ( Chen et al, 2020 ). The concentration and time of 6-OHDA intervention at 50% cell activity were selected as the experimental conditions.…”
Section: Methodsmentioning
confidence: 99%